SLR Study: Plastic Waste Recycling Innovation as a Science Learning Medium in Elementary Schools - Maghfirotul Firmaning Lestari; Saihan Saihan; Lailatul Usriyah (UIN Raden Mas Said Surakarta, 2025)
Learning innovation based on plastic waste recycling is a relevant contextual approach to improve science learning while instilling environmental awareness in elementary schools. This study aims to systematically analyze the types of learning innovations, media forms, impacts, and challenges of implementing plastic waste recycling as a science learning medium in elementary schools. The research method used is a Systematic Literature Review (SLR) of national scientific articles published between 2019 and 2025. Literature searches were conducted through Google Scholar, Garuda, DOAJ, and SINTA databases with relevant keywords. Selected articles were analyzed using thematic analysis and synthesized descriptively-qualitatively. The results of the study indicate that learning innovations include innovative learning media, interactive media, STEAM-based projects, P5 thematic learning, and collaborative activities based on sustainable education. The resulting media include ecobricks, educational board games, literacy trees, lapbooks, and creative products from used plastic. The implementation of these innovations positively impacts students' understanding of science concepts, learning outcomes, scientific literacy, creativity, and problem-solving skills. However, challenges remain in teacher preparedness, limited time and resources, and a lack of understanding of the economic aspects of recycled products. This study's findings confirm that using recycled plastic waste can be an effective and sustainable medium for science learning in elementary schools when supported by adequate planning and guidance.